Answer:
C) x = -6
Explanation:
We are given two functions and asked to find which input produces the same output.
We need to plug in each of the given values in the two functions and find the outputs.
f(x) = 2/3x + 7 and g(x) = 2x + 15
Plugin x = -12 and find the outputs
f(-12) = (2/3)(-12) + 7 ; g(-12) = 2(-12) + 15
f(-12) = -8 + 7 ; g(-12) = -24 + 15
f(-12) = -1 ; g(12) = -9
Plugin x = -9 and find the outputs
f(-9) = (2/3)(-9) + 7 ; g(-9) = 2(-9) + 15
f(-9) = -6 + 7 ; g(-9) = -18 + 15
f(-9) = 1 ; g(-9) = -3
Plugin x = -6 and find the outputs
f(-6) = (2/3)(-6) + 7 ; g(-6) = 2(-6) + 15
f(-6) = -4 + 7 ; g(-6) = -12 + 15
f(-6) = 3 ; g(-6) = 3
When x = -6, the output value of the two functions are the same.
Therefore, the answer is C) x = -6